2015
DOI: 10.1590/1414-462x201500020045
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneidade de comportamentos de risco para a saúde e fatores associados em estudo de base populacional

Abstract: ResumoObjetivoVerificar a prevalência simultânea de comportamentos relacionados à saúde e analisar a sua associação com condições sociodemográficas e de saúde na população com 40 anos ou mais de idade de um município de médio porte da região Sul do Brasil.MétodosTrata-se de um estudo de base populacional. Os comportamentos de risco investigados foram: inatividade física no lazer, consumo irregular de frutas e de verduras, tabagismo e consumo abusivo de álcool. As variáveis dependentes do estudo foram o somatór… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
1
12
0
16
Order By: Relevance
“…Similar data have been observed in another study in Cambé, Paraná, Brazil, that among the examined risk factors, the prevalence was higher in relation to physical inactivity and obesity. 13 Other researches in the same municipality showed that physical inactivity was more prevalent (71.3%) followed by low or moderate consumption of fruits and vegetables (63.1%), smoking (19.7%) and abusive consumption of alcohol (18.2%), 7,14 being that women showed negative behavior (52.3%), being prevalent in lower economic classes, with lower educational level and age between 40 and 49 years, 15 similar to our findings. Research conducted in the northeastern of Brazil, show that 56.9 percent of women did not practice physical activity, and 32% practiced up to twice a week, 16 being the results similar to our study's results.…”
Section: Health Indicators and Daily Habitsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similar data have been observed in another study in Cambé, Paraná, Brazil, that among the examined risk factors, the prevalence was higher in relation to physical inactivity and obesity. 13 Other researches in the same municipality showed that physical inactivity was more prevalent (71.3%) followed by low or moderate consumption of fruits and vegetables (63.1%), smoking (19.7%) and abusive consumption of alcohol (18.2%), 7,14 being that women showed negative behavior (52.3%), being prevalent in lower economic classes, with lower educational level and age between 40 and 49 years, 15 similar to our findings. Research conducted in the northeastern of Brazil, show that 56.9 percent of women did not practice physical activity, and 32% practiced up to twice a week, 16 being the results similar to our study's results.…”
Section: Health Indicators and Daily Habitsmentioning
confidence: 96%
“…As the results of our study, there are similar data, highlighting obesity, hypertension, low HDL, unhealthy diet and sedentary lifestyle related as risk behaviors and social capital. 1,7,14,15,[18][19][20][21][22][23][24] Despite all these data, studies have evidenced that CNTD mortality rate showed a tendency for reduction of about 20% since the 1990's, being observed larger reductions in cerebrovascular, chronic respiratory and ischemic disorders. The authors attribute this reduction to PHC's expansion, covering more than 60% of the population, improving access to healthcare and the significant reduction for prevalence of smoking in Brazil, from 34.8% (1989) to 8.7% (2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, a associação positiva entre o envolvimento em brigas e estado civil com um companheiro é contrária àquela observada em estudos prévios 38,39 . Geralmente, os indivíduos que possuem um companheiro tendem a uma condição afetiva mais estável, com hábitos e comportamentos mais sensatos 40 . É importante ressaltar que, apesar de a amostra ter sido de uma única universidade, os resultados são representativos de CRS entre estudantes universitários no norte de Minas.…”
Section: Nrea (%) Bcfv (%) Ce (%) Tbd (%) Caba (%) CDI (%) Eb (%) Uipunclassified
“…Entre os transtornos associados ao uso de substâncias, destacam-se perda de memória, baixo desempenho escolar ou no trabalho, distúrbios físicos e psicológicos, dependência na vida adulta, suicídio, acidentes ou violência culminando em trauma, como o traumatismo facial e dentário [5][6][7][8][9][10][11][12] . O traumatismo dentário (TD) pode ser definido como qualquer injúria de natureza térmica, química ou física que afete o dente e representa, dentre as alterações bucais, um dos mais sérios problemas de saúde pública em crianças e adolescentes 13 .…”
Section: ▄ Introduçãounclassified